Emerging roles and responsibilities of libraries in support of reproducible research - Schmidt, Birgit; Chiarelli, Andrea; Loffreda, Lucia; Sondervan, Jeroen (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2024)
Ensuring the reproducibility of research is a multi-stakeholder effort that comes with challenges and opportunities for individual researchers and research communities, librarians, publishers, funders and service providers. These emerge at various steps of the research process, and, in particular, at the publication stage.Previous work by Knowledge Exchange highlighted that, while there is growing awareness among researchers, reproducible publication practices have been slow to change. Importantly, research reproducibility has not yet reached institutional agendas: this work seeks to highlight the rationale for libraries to initiate and/or step up their engagement with this topic, which we argue is well aligned with their core values and strategic priorities.We draw on secondary analysis of data gathered by Knowledge Exchange, focusing on the literature identified as well as interviews held with librarians. We extend this through further investigation of the literature and by integrating the findings of discussions held at the 2022 LIBER conference, to provide an updated picture of how libraries engage with research reproducibility.Libraries have a significant role in promoting responsible research practices, including transparency and reproducibility, by leveraging their connections to academic communities and collaborating with stakeholders like research funders and publishers. Our recommendations for libraries include: i) partnering with researchers to promote a research culture that values transparency and reproducibility, ii) enhancing existing research infrastructure and support; and iii) investing in raising awareness and developing skills and capacities related to these principles.